THE REALITIES OF THE GLOBALIZATION - THE TRANSLATIONS AND LINGUISTIC INTERPRETATION. - TUDUCE, Florina-Gabriela (Studii de Ştiintă şi Cultură, 2018)
Globalization, as well as internationalisation are very important issues of our times, during these processes we make strong connections to other people all over the world, using English language to express ourselves and the art of translation and interpretation become more and more important. Globalization is positively needed by the society and country to go ahead and become a developed society and nation, it has implications for all levels of education. On the other hand, internationalisation is a comprehensive process, in permanent evolution and must be carried out with energy and firmness by the entire school community and by all its entities. Dealing with internationalisation, you also experience translation and interpreting, both of them having a great importance in the process.